Improved herbicide selectivity in tomato by safening action of benoxacor and fenclorim - Castro, Edicarlos [UNESP]; Pucci, Carolina [UNESP]; Duarte, Stefano; Burgos, Nilda Roma; Tseng, Te Ming (Cambridge Univ Press, 2020)
Safeners have been widely used to reduce phytotoxicity to crops, thus serving as an alternative weed control strategy. Benoxacor and fenclorim safeners have the potential to protect plants from herbicide phytotoxicity by increasing glutathione S-transferase (GST) activity within the plant. The study aimed to evaluate the safening effect of benoxacor and fenclorim on tomato against selected herbicides applied POST. The experiment was conducted in a greenhouse in a completely randomized designed with four replications in a 9 x 3 factorial scheme, where Factor A consisted of eight herbicides including a nontreated control, and Factor B consisted of two safeners including a nontreated control. The herbicide treatments were sulfentrazone (0.220 kg ai ha(-1)), fomesafen (0.280 kg ai ha(-1)), flumioxazin (0.070 kg ai ha(-1)), linuron (1.200 kg ai ha(-1)), metribuzin (0.840 kg ai ha(-1)), pyroxasulfone (0.220 kg ai ha(-1)), and bicyclopyrone (0.040 kg ai ha(-1)). Safener treatments consisted of benoxacor (0.67 g L-1) and fenclorim (10 mu M). Tomato seeds were immersed in safener solution before sowing and herbicides were applied when tomato plants were at the 3-leaf stage, or 25 days after sowing. Visible injury was scored at 3, 7, 14, and 21 d after application (DAA), and shoot biomass was recorded 21 DAA. Seed treatment with fenclorim reduced injury caused by imazamox and bicyclopyrone by 5.5 and 1.3 times, respectively, whereas benoxacor reduced the injury from bicyclopyrone 1.3 times. In addition, tomato plants pretreated with fenclorim showed a lesser reduction in biomass after application of imazamox, fomesafen, and metribuzin, whereas plants pretreated with benoxacor showed lesser biomass reduction after metribuzin application. Thus, the use of safeners promotes greater crop selectivity, allowing the application of herbicides with different mechanisms of action on the crop.
Keywords: Crop protection; glutathione S-transferase; weed control; specialty crop; herbicide selectivity